Self-Reported Food Handling Behaviors of U.S. Consumers While Grilling Poultry and Meat - Taylor Terry; Edgar Chambers; Sandria Godwin; Edgar Chambers (Foods)
Every year, 48 million people in the United States are affected by foodborne illnesses. Twenty-five percent of reported foodborne illnesses are due to unsafe food behaviors in the home. Consumers are grilling more frequently throughout the year; however, little is known about their food handling practices when doing so. Therefore, it is important to investigate the food safety practices of consumers when using an outdoor grill to prepare meat and poultry. A nationwide web survey of consumers who grill outdoors (n = 1024) was conducted to approximate the percentage of consumers following recommended food handling practices while grilling. Results showed that there was low adherence to not washing meat/poultry, using separate or clean utensils after flipping or turning the meat or poultry on the grill, or using a thermometer to determine doneness. Sixty-three percent of respondents washed meat or poultry before grilling. Only 22% reported washing utensils after turning or moving the poultry or meat on the grill, which can cause potential cross- or re-contamination. Consumers used many techniques to determine the doneness of meat/poultry, but only 25.6% used a thermometer. The results differed by some demographic characteristics. Women and respondents who grilled poultry versus meat were more likely to follow safe food handling practices. This survey indicates that food safety educators should focus strongly on cross- or re-contamination and thermometer use when designing food safety content for the grilling population.